PENGARUH SAJIAN INFORMASI DAN TERPAAN INFORMASI AKUN INSTAGRAM TERHADAP SIKAP FOLLOWERS MENGENAI PENGELOLAAN SAMPAH: Survei Pada Followers @waste4change - Hereditha Alifia, (2023)
In 2021, Ministry of Environment and Forestry released a "Capaian Kinerja Pengelolaan Sampah" data where they stated there was a waste generation from 201 cities/regencies in Indonesia amounting 41.807.931,40 tons/year. Those numbers showed that waste has became a serious environmental issue faced by Indonesia. In this era of rapidly developing technology, issues in society can be raised through social media, similarly to what Waste4Change Indonesia does where they frequently present information to virtual society regarding waste issues and ways to handle it. This research discusses how presented information on social media and information exposure activity can affect readers' attitude on waste management where it is supported by Information Integration Theory. This study is a quantitative research with explanative type of quantitative approach. This research used survey method to gather data through questionnaire that was distributed to 100 respondents who are followers of @waste4change Instagram account and actively exposed to the information. The result of this study showed that there was an effect between information presentation and information exposure of Instagram account to followers' attitude on waste management simultaneously by 58.4%. Based on the result of hypothesis testing, the result showed that Ha was accepted and H0 was rejected.